Some flies do not play ping-pong. - Fridrich, A.; Moran, Y. (PLoS Biology, 2023)
Genome integrity in animals depends on silencing of mobile elements by Piwi-interacting RNAs (piRNAs). A new study in this issue of PLOS Biology reveals recent evolutionary losses of key piRNA biogenesis factors in flies, highlighting adaptability by rapid shift to alternative piRNA biogenesis strategies.